New Trends in E-service and Smart Computing (Studies in Computational Intelligence, 2018)
This book examines theoretical and practical aspects of emerging technologies in e-service and artificial intelligence from an academic and professional viewpoint. To do so, it focuses on three major areas: the development of novel user support systems; development of smart mobility; and emerging technologies in Artificial Intelligence (AI). With regard to the development of novel user support systems, Chapter 1 introduces alternative ingredients recommendation using data on co-occurrence relation and ingredients categories to support cooking, while Chapter 2 introduces a study on location information inference using data acquired by low-energy Bluetooth devices. Turning to the development of smart mobility, Chapter 3 highlights a sustainable information infrastructure project for smart mobility systems. In addition, Chapter 4 presents a lifecycle-oriented development process to improve requirements and design in terms of uncertainties to provide sustainable information architectures for smart mobility. In the book's third and last part - emerging technologies in AI - Chapter 5 presents a summarization task for sports events on Twitter, focusing on an abstractive approach based on sub-events during the sports event. Chapter 6 discusses the generation of headlines using a recurrent neural network based on a machine translation approach. Lastly, Chapter 7 explores customer behavior analysis using enthusiasm analysis, an approach that estimates customers' activation levels. The book gathers a selection of the highest-quality papers presented at the 4th International Congress on Advanced Applied Informatics, held on July 12-16, 2015 in Okayama, Japan. Given the breadth of its coverage, it offers a valuable resource for practitioners, researchers and students alike.